Penyusunan Perangkat Pembelajaran Kurikulum Merdeka di SMKS Mandiri Kraksaan Probolinggo - Ilmawan, Cilda Thesisa; Nurafini, Fira; El-Yunusi, Muhammmad Yusron; Safira, Mirza Elmy; Rodiyah, Siti Kholidatur; Retnowati, Eli; Mardikaningsih, Rahayu; Darmawan, Didit; Masnawati, Eli; Munir, Misbachul (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Changes in trends in education in the era of independent learning emphasize the importance of the teacher's role as the main goal in developing learning tools according to demands. In the independent curriculum, making teaching modules is mandatory for vocational subject teachers. This module is used as an interactive learning media that helps teachers when teaching. Basically, teaching modules are made by teachers with the aim of being teaching materials as well as exercises for assessing students' knowledge, skills and attitudes. For this reason, the competency improvement workshop for the preparation of independent learning curriculum learning tools for educators at the Mandiri Kraksaan Probolinggo Vocational High School aims to provide training and assistance to educators at the Mandiri Kraksaan Probolinggo Vocational High School in the preparation of teaching learning modules based on the independent learning curriculum. at SMKS Mandiri Kraksaan Probolinggo. Service activities were carried out with the participation of 10 teachers. The results of the identification of the problems found during observation by the community service team (PKM) from Sunan Giri University Surabaya towards the Mandiri Kraksaan Probolinggo Vocational High School, namely that not all teachers who teach understand and design the learning process properly in accordance with the applicable curriculum, due to the lack of training obtained.